2004
DOI: 10.1038/sj.emboj.7600262
|View full text |Cite
|
Sign up to set email alerts
|

Two-substrate association with the 20S proteasome at single-molecule level

Abstract: The bipartite structure of the proteasome raises the question of functional significance. A rational design for unraveling mechanistic details of the highly symmetrical degradation machinery from Thermoplasma acidophilum pursues orientated immobilization at metal-chelating interfaces via affinity tags fused either around the pore apertures or at the sides. End-on immobilization of the proteasome demonstrates that one pore is sufficient for substrate entry and product release. Remarkably, a 'deadend' proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 44 publications
2
44
0
5
Order By: Relevance
“…Binding of the first would therefore trigger binding of the second, third, and fourth substrate molecules. This is in accord with a previous proposal for cooperative binding of a much smaller protein (insulin); however, only binding in both antechambers, and not the central cavity, was considered (35). Additionally, atomic force microscope measurements have indicated a two-state model of allosteric transition that is dependent on substrate binding (40).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Binding of the first would therefore trigger binding of the second, third, and fourth substrate molecules. This is in accord with a previous proposal for cooperative binding of a much smaller protein (insulin); however, only binding in both antechambers, and not the central cavity, was considered (35). Additionally, atomic force microscope measurements have indicated a two-state model of allosteric transition that is dependent on substrate binding (40).…”
Section: Discussionsupporting
confidence: 74%
“…We also noted the formation of dimeric forms of the proteasome after loss of ␣-subunits and substrate, a process not observed for the free proteasome. This implies that a conformational change is induced upon substrate binding and translocation, as suggested by other studies (35)(36)(37), and that this allosteric transition persists even after loss of ␣-subunit and substrate. The finding that the FIGURE 7.…”
Section: Discussionmentioning
confidence: 62%
“…Such trans-splicing is conceivable in theory, because it was shown that the inner channel of the proteasome, with a diameter of 13 Å (17), can accommodate more than one polypeptide chain (18,19). The proteasome was also able to bind and process two substrates simultaneously: one in each catalytic chamber (20). To test this hypothesis, we designed plasmids encoding full-length FGF-5 proteins containing a point mutation in fragment NTYAS or PRFK.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Hier zeigen wir erstmals den Einsatz von kleinen synthetischen Verbindungen, die gewissermaßen als Torwächter die proteolytische Aktivität des Proteasomkomplexes kontrollieren. Ein multivalenter Chelatorkopf (multivalent chelator head, MCH) mit vier NTA-Gruppen (tetrakisNTA, Schema 1 c) wird zur Vernetzung der Histidin-Markierungen (His-Tags) verwendet, die entweder an den N-terminalen Regionen der a-Untereinheiten rund um die beiden Öff-nungen (aN-His 6 -Proteasom) oder an den C-Termini der bUntereinheiten an der Seite des Proteasoms (bC-His 6 -Proteasom, Schema 1 b) lokalisiert sind.…”
unclassified